Profil Kepribadian Guru Bimbingan Konseling (BK) Berdasarkan Kriteria Peserta Didik fase F (Gen Z) - Nurul Nasywah Aufa Nst (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
A guidance and counseling teacher is a counselor/guide who works to help students through counseling. Guidance and Guidance Teachers must have a personality that is able to adapt to the needs of Phase F (Gen Z) students. This research aims to determine the personality of guidance and counseling teachers based on the criteria desired by phase F (Gen Z) students at Al Manar Medan Private High School. This research was conducted at Al Manar Private High School, Medan. With a sample of 3 students and 2 guidance and counseling teachers. This type of research is qualitative research. Data collection techniques use interview techniques with research instruments in the form of interview guides. The data obtained is analyzed by making a transcript, then the researcher must be careful and then reduce the data in order to draw conclusions. Based on the data obtained, it can be seen that guidance and counseling teachers have a very important role. And students in phase F (gen Z) have their own criteria for personality that a guidance and counseling teacher must have so that guidance and counseling activities at school run well. It can be concluded that the criteria for phase F (gen Z) students regarding the personality of a guidance and counseling teacher are having an honest, trustworthy, friendly personality, being able to keep secrets, being patient, being sensitive to students, praying warmly, always smiling, respecting everyone, having broad knowledge, caring, able to get closer and familiarize themselves with students and fun to socialize with or communicate with students.